Noninvasive Evaluation of EGFR Expression of Digestive Tumors Using 99mTc-MAG3-Cet-F(ab′)2-Based SPECT/CT Imaging. (24th June 2022) - Shi, Dai; Zhang, Yiqiu; Xu, Zhan; Si, Zhan; Cheng, Yuan; Cheng, Dengfeng; Liu, Guobing
Abstract : Purpose . This study is aimed at investigating the feasibility of cetuximab (Cet) F(ab ′ )2 fragment- (Cet-F(ab ′ )2 -) based single photon emission tomography/computed tomography (SPECT/CT) for assessing the epidermal growth factor receptor (EGFR) expression in digestive tumor mouse models. Methods. Cet-F(ab ′ )2 was synthesized using immunoglobulin G-degrading enzyme of Streptococcus pyogenes (IdeS) protease and purified with protein A beads. The product and its in vitro stability in normal saline and 1% bovine serum albumin were analyzed with sodium dodecyl sulfate–polyacrylamide gel electrophoresis. The EGFR expression in the human colon tumor cell line HT29 and the human stomach tumor cell line MGC803 were verified using western blotting and immunocytochemistry. Cet-F(ab ′ )2 was conjugated with 5(6)-carboxytetramethylrhodamine succinimidyl ester to demonstrate its binding ability to the MGC803 and HT29 cells. Cet-F(ab ′ )2 was conjugated with NHS-MAG3 for 99m Tc radiolabeling. The best imaging time was determined using a biodistribution assay at 1, 4, 16, and 24 h after injection of the 99m Tc-MAG3 -Cet-F(ab ′ )2 tracer. Furthermore, 99m Tc-MAG3 -Cet-F(ab ′ )2 SPECT/CT was performed on MGC803 and HT29 tumor-bearing nude mice. Results. HT29 cells had low EGFR expression while MGC803 cell exhibited the high EGFR expression. Cet-F(ab ′ )2 and intact cetuximab showed similar high binding ability to MGC803 cells but not to HT29 cells. Cet-F(ab ′ )2 and 99m Tc-MAG3 -Cet-F(ab ′ )2 showed excellent in vitro stability. The biodistribution assay showed that the target to nontarget ratio was the highest at 16 h (17.29 ± 5.72, n = 4 ) after tracer injection. The 99m Tc-MAG3 -Cet-F(ab ′ )2 -based SPECT/CT imaging revealed rapid and sustained tracer uptake in MGC803 tumors rather than in HT29 tumors with high image contrast, which was consistent with the results in vitro. Conclusion. SPECT/CT imaging using 99m Tc-MAG3 -Cet-F(ab ′ )2 enables the evaluation of the EGFR expression in murine EGFR-positive tumors, indicating the potential utility for noninvasive evaluation of the EGFR expression in tumors.